Reforming Children's Health Care in the Soviet Union after the World War II - Valeriy Yu. Albitskiy; Stella A. Sher ("Paediatrician" Publishers LLC, 2023)
The article presents the results of historical and medical research reflecting the issues of reforming children's health care after the World War II. The aim of the study is to present the problems of reforming children's health care in the USSR in the post-war decade (1946-1956). The study relevance is defined by necessity to examine the historical experience of reforming children's health care during the most difficult for our country post-war period so we can learn crucial lessons from the past and use them further for the successful implementation of the federal project "Development of children's health care, including the creation of modern infrastructure for medical care provision for children". Published and unpublished documents of the USSR Ministry of Health and the USSR Academy of Medical Sciences, stored in the State Archive of the Russian Federation, as well as publications from medical journals, scientific collections, monographs were studied to cover this issue. The analysis of this study has shown that the most significant part in the state health reform started in the first post-war years was the merger of hospitals and clinics for adults, maternity hospitals with women's consultations, children's hospitals with children's consultations and outpatients' clinics. The post-war reform has contributed to the improvement of the quality of inpatient and outpatient medical care, to the increasing role of the hospital as the organizing and leading center of all united facilities. The integration of children's hospitals with consultations and outpatients' clinic, as well as the organization of the primary pediatric care according to the system of medical and preventive care provision for children aged from birth to 16 years by single pediatrician, have shown succession in the work of primary care doctors and hospitals. The increase in the health workers qualifications, the development of specialized types of medical care, the improvement in the quality of medical and preventive care were observed. The reform of children's health care contributed to the diseases' timely diagnosis and early patients' hospitalization, strengthening the connection of the primary care doctor and nurse with the child's family, and decreasing of child morbidity and mortality.